2008
DOI: 10.1093/molbev/msn187
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Paleopolyploidizations during the Evolution of the Compositae Reveal Parallel Patterns of Duplicate Gene Retention after Millions of Years

Abstract: Of the approximately 250,000 species of flowering plants, nearly one in ten are members of the Compositae (Asteraceae), a diverse family found in almost every habitat on all continents except Antarctica. With an origin in the mid Eocene, the Compositae is also a relatively young family with remarkable diversifications during the last 40 My. Previous cytologic and systematic investigations suggested that paleopolyploidy may have occurred in at least one Compositae lineage, but a recent analysis of genomic data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
410
1
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 326 publications
(437 citation statements)
references
References 58 publications
25
410
1
1
Order By: Relevance
“…However, studies on the Compositae (Asteraceae) lineage showed that duplicated genes generated by WGD were significantly enriched for genes associated with structural components or cellular organization, and regulatory and developmental genes such as transcription factors were significantly underrepresented. This pattern was almost consistent in all Compositae species investigated (Barker et al, 2008). Together, these observations suggest that some underlying mechanisms might have contributed to the evolutionary fates of duplicated genes derived from WGD events across divergent taxa, although selection forces might be varied substantially among higher taxonomic categories.…”
supporting
confidence: 65%
“…However, studies on the Compositae (Asteraceae) lineage showed that duplicated genes generated by WGD were significantly enriched for genes associated with structural components or cellular organization, and regulatory and developmental genes such as transcription factors were significantly underrepresented. This pattern was almost consistent in all Compositae species investigated (Barker et al, 2008). Together, these observations suggest that some underlying mechanisms might have contributed to the evolutionary fates of duplicated genes derived from WGD events across divergent taxa, although selection forces might be varied substantially among higher taxonomic categories.…”
supporting
confidence: 65%
“…Recent gene family expansion has also been described for the FT/TFL1 family (Blackman et al 2010). Some of these expansions likely result from persistence of duplications that arose during polyploidy events at the base of the Compositae or, more recently, within the Heliantheae (Barker et al 2008). For example, values of K s , the synonymous substitution rate between two sequences, for sunflower duplicate pairs of ZTL and FKF1 were 0.71 and 0.66, respectively, consistent with the former event; K s was 0.45 for one of the duplication events in the sunflower FT clade, consistent with the latter event.…”
Section: Flowering Time Gene Homologs In Sunflowermentioning
confidence: 93%
“…Several lineagespecific WGD events thus far documented across the angiosperms (Tang et al, 2008;Jaillon et al, 2009;Soltis et al, 2009) represent only the tip of the iceberg, as potential other WGD events remain uncovered. We envisage that more mesopolyploid WGDs will be revealed in Brassicaceae and other families, such as Asteraceae, where differently aged polyploidization events (Barker et al, 2008) and descending dysploidy have a prominent role in the genome evolution.…”
Section: Mesopolyploid Wgdmentioning
confidence: 99%
“…Multiple and often lineage-specific WGD events uncovered in Asteraceae (Barker et al, 2008), Cleomaceae Barker et al, 2009), Solanaceae (Schlueter et al, 2004), and other taxa (Soltis et al, 2009) imply a key role of WGDs in the evolution of land plants. The steadily improving knowledge of crucifer genome evolution suggests that the duplication-diploidization process is ongoing and occurred several times across the family.…”
Section: Introductionmentioning
confidence: 99%